2014
DOI: 10.1371/journal.pone.0106943
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation in the Dorsolateral Prefrontal Cortex Changes Subjective Evaluation of Percepts

Abstract: Nelson and Narens have proposed a metacognition model that dissociates the objective processing of information (object-level) and the subjective evaluation of the performance (i.e., the metalevel). Neurophysiological evidence also indicates that the prefrontal cortices (PFC) are the brain areas which perform the metalevel function [1]–[3]. A corresponding neural mechanism of Nelson and Narens’s model, called dynamic filtering theory [4], [5], indicates that object-level processing is distributed in the posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…For example, dlPFC has been implicated in both the perceptual decision (Philiastides et al, 2011;Rahnev et al, 2011a;Hunt et al, 2015;Georgiev et al, 2016) and confidence (Lau and Passingham, 2006;Rounis et al, 2010;Chiang et al, 2014;Shekhar and Rahnev, 2018). Our results suggest that at least a subregion of dlPFC is in fact more active during confidence compared to decision processes.…”
Section: Brain Areas More Active In Confidence Judgmentsmentioning
confidence: 62%
“…For example, dlPFC has been implicated in both the perceptual decision (Philiastides et al, 2011;Rahnev et al, 2011a;Hunt et al, 2015;Georgiev et al, 2016) and confidence (Lau and Passingham, 2006;Rounis et al, 2010;Chiang et al, 2014;Shekhar and Rahnev, 2018). Our results suggest that at least a subregion of dlPFC is in fact more active during confidence compared to decision processes.…”
Section: Brain Areas More Active In Confidence Judgmentsmentioning
confidence: 62%
“…Finally, there are also numerous studies showing that TMS and lesion to human PFC can affect many other aspects of visual perception (Barceló et al, 2000;Turatto et al, 2004;Ruff et al, 2006;Philiastides et al, 2011;Lee and D'Esposito, 2012;Ritzinger et al, 2012;Chiang et al, 2014;Rahnev et al, 2016), and more recent neuropsychological work has demonstrated that individuals with unilateral damage to PFC often display pronounced deficits on visual tasks. For example, Barceló et al (2000) showed that individuals with unilateral focal lesions in the lateral prefrontal cortex exhibited impairments in the ability to regulate dependent activity in extrastriate regions and detect visual targets in the visual field contralateral to the damage.…”
Section: Fig 3 Lesion To Pfc Specifically Impairs Subjective Percepmentioning
confidence: 99%
“…Recently, neuromodulation therapy has been clinically recommended for treating cognitive deficits in psychiatric disorders [64][65][66][67][68]. Our results in this study may suggest that prefrontal modulation in OD patients might be treated by using repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) in a dental clinic.…”
Section: Discussionmentioning
confidence: 76%